Investigation of the effects of chitosan-zinc nanoparticles Ch-ZnO NPs on phenotypic biofilm formation of Acinetobacter baumannii and cytotoxicity assay - Abdul Jabbar, Yousif Salih; Gazi, Umut; Ahmed, Mais Emad (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
The research aimed to create chitosan zinc oxide nanoparticles (Ch-ZnO NPs) for use as agents to combat biofilms produced by Acinetobacter baumannii. The Ch-ZnO NPs were produced using chitosan biomass as a cost-effective, eco-friendly material for synthesis purposes. The properties of the produced nanoparticles were analyzed through a range of methods. Fourier transform infrared spectroscopy (FTIR) carried out chemical structure identification and analysis. The maximum absorption peak, at 235 nm was confirmed through UV spectrophotometry. The X-ray diffraction (XRD) varied the hexagonal crystal structure with a particle size measurement of 34 nm. Surface morphology was probed using atomic force microscopy (AFM) and field emission scanning electron microscopy (FESEM). Further details on the particle structure were obtained through high-resolution transmission electron microscopy (HR‐TEM).   To assess how Ch-ZnO NPs perform in real-world scenarios when dealing with Acinetobacter baumannii bacterial infections and tackling biofilms effectively was the focus of the study, with exploration into its impact on cytotoxicity using the cell line model of A375 for potential medical applications. The research findings indicated that Ch-ZnO NPs exhibited capabilities in inhibiting biofilm growth from drug-resistant Acinetobacter baumannii bacteria strains with an IC50 concentration of 2.0 g/mL. The assessment of cell mortality rates highlighted a rise, in cell death among the treated cells from the application of Ch-ZnO NPs. The research revealed that Ch-ZnO NPs demonstrated ant-biofilm properties and cytotoxic effects, which suggest their potential for use is significant. This study emphasizes the promise of Ch-ZnO NPs as an efficient option for treating infections resistant to multiple antibiotics.